Promoting teachers’ technology professional development through laptops - Md. Khambari, Mas Nida; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi (Universiti Putra Malaysia Press, 2012)
This paper reports on a survey study that was carried out to determine the impact levels of laptops use on teachers’ technology professional development. Teachers’ technology professional development is approached as a constructivism process that demands teachers to learn how to use technology and apply them in their daily routines. Teachers in this study were granted laptops from the Teaching-Learning of Science and Mathematics in English (PPSMI) programme. Hence, they were regarded as the early adopters of technology innovation in schools, and became the agents of change. It is believed that playing the teachers’ role as the agents of change has contributed on a significant change in their practice. Based on the notion, this study was conducted to reveal the impacts of laptop use by teachers on their professional development. A survey was carried out among 386 laptop teachers using a set of questonnaire that measures the impact from four dimensions; namely teaching-learning, the use of resources, communication and sharing of information, and teachers’ laptop competency. The findings explicate that teachers’ use of laptop has a moderate impact on their technology professional development.